Implementing neuropsychological rehabilitation following severe traumatic brain injury in a low-to-middle income country: a case report - Soule, Alexa Caitlin; Fish, Taryn Jane; Winegardner, Jill; Schrieff-Brown, Leigh (Frontiers in Rehabilitation Sciences, 2024)
IntroductionTBI incidence and distribution are largely overrepresented in low- to middle-income countries (LMICs), such as South Africa (SA), with substantial associated human and financial costs. However, access to rehabilitation for the public is severely limited and not standard practice in SA. Given this background, studies demonstrating the successful implementation of neuropsychological rehabilitation in a LMIC setting are important. Published studies of this nature are generally lacking in this context. Further, there is a need to evaluate interventions that can be implemented at a low cost. To this end, we report on a neuropsychological rehabilitation program for an individual with severe TBI in a LMIC context, aimed at improving his capacity for activities of daily living.MethodA 33-year-old, South African male who sustained a severe traumatic brain injury (TBI) partook in a neuropsychological intervention aimed at remediating functional deficits and enhancing independent functioning. The intervention utilised principles of Goal Management Training and external memory aids, with reliance on procedural memory and errorless learning, to target the participant's impairments in executive functioning and memory through the use of assistive technology—namely smart device applications.ResultsData collected pre- and post-intervention on formal neuropsychological measures demonstrated no significant change in cognition. However, observational data and qualitative feedback from the participant's family indicated notable improvement in performance on everyday tasks with reduced number of errors and reduced need for external prompting whilst completing intervention tasks across sessions.DiscussionIn the context of severe TBI, neuropsychological rehabilitation can facilitate gains in independent functioning. This study provides support for the value of neurorehabilitation especially for interventions that can be rolled out at low cost and should serve as impetus for further such research in South Africa, where neuropsychological rehabilitation infrastructure and services are lacking.